2008
DOI: 10.1056/nejmoa0707571
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin during Coronary-Artery Bypass Grafting and Risk of Death

Abstract: Patients who received aprotinin alone on the day of CABG surgery had a higher mortality than patients who received aminocaproic acid alone. Characteristics of neither the patients nor the surgeons explain the difference, which persisted through several approaches to control confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
240
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(246 citation statements)
references
References 31 publications
5
240
0
1
Order By: Relevance
“…An example of this is seizure attacks in some patients. Aprotinin, a plasmin inhibitor in limited use in some countries, also suffers from a lack of specificity [1,5,6]. Several plasmin inhibitors being developed as antifibrinolytics include KDI-L17R [15] textilinin-1 [16] and cyclic peptidomimetics [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this is seizure attacks in some patients. Aprotinin, a plasmin inhibitor in limited use in some countries, also suffers from a lack of specificity [1,5,6]. Several plasmin inhibitors being developed as antifibrinolytics include KDI-L17R [15] textilinin-1 [16] and cyclic peptidomimetics [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…A direct plasmin inhibitor, which is approved for use in only few countries, is aprotinin. Although useful, aprotinin, a Kunitz-type plasmin inhibitor, was withdrawn from the clinic in the U.S. due to its high risk of mortality and morbidity [5,6]. The two lysine analogs also suffer from significant adverse effects arising from their effects on the central GABA receptor, which provokes convulsive seizures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Premier's methodology and database, in which individualized severity-adjusted expected outcome parameters are calculated for each patient, are regularly used to evaluate mortality, costs, complications, morbidity, and resource utilization across a wide variety of patients and disease states [21,[24][25][26][27][28]. In this study, we focused on illnesses related to poisoning or toxic effects of drugs and demonstrated that inpatients primarily cared for by medical toxicologists, compared to patients primarily cared for by non-toxicologists and adjusted for predicted values, experienced significantly shorter hospital stays, generated lower costs, and suffered lower mortality.…”
Section: Discussionmentioning
confidence: 99%
“…34 Instrumental variable methods or quasi-experimental designs can also be used to generate unbiased estimates in some situations. 23,35,36 Dose-response relationships can be tested to better assess the strength of the relationship between the preventive therapy and the outcome in question. Additionally, researchers can restrict the study to a population that is likely to be more homogenous with regard to health-seeking status to assess if there is a difference in result.…”
Section: Evaluating Study Design and Adjustment Methodsmentioning
confidence: 99%